OPHIOLITE OBDUCTION PULSES AS A PROXY INDICATOR OF SUPERPLUME EVENTS? - Vaughan A.P.M.; Scarrow J.H. (My University, 2003)
A major new synthesis of ophiolite geochronology and map of global Phanerozoic distribution indicates that previously noted pulses of ophiolite obduction can be linked to superplume-related tectonism. A marked cyclicity is evident in obduction ages obtained from minerals in ophiolite metamorphic soles and obduction-related minor intrusions. This episodicity is in phase with periods of predominantly uniform polarity of the geomagnetic field, formation of massive carbon-rich deposits, sea-level highstands, and formation of large flood basalt provinces; all generally considered to be superplume proxy indicators. A key to interpreting ophiolite obduction as a further proxy is the mid-Cretaceous, superplume-associated, ocean-margin compressional deformation. During this event, thermal rejuvenation and increased buoyancy of ocean lithosphere caused arc–terrane collision, marginal-basin shoaling, back-arc basin closure and ophiolite obduction. Convergent margins were placed in compression with increased coupling between subducting and overriding plates resulting in major ocean margin deformation. Being directly datable and tectonically and petrologically distinctive makes ophiolite assemblages of considerable use for identifying superplume events.